Large grid integration of small residential photovoltaic cells. - Capatina, Octavian (Cambridge Scholars Publishing, 2020)
This book, through step-by-step modelling and simulation, demonstrates why the large integration of small residential roof-mounted photovoltaic cells into the public grid is one of the best solutions to mankind's energy problems, given the consequent low impact on power systems' dispatching centres. It introduces and develops a new concept of renewable energy: the simultaneous operation on/off grid of the energy cell, with a triple function inverter (on-grid, off-grid and charger). The text highlights the advantages and superiority of the large integration of small residential widespread photo.